THE APPLICATION OF USHUL FIQH TO MECHANICAL SLAUGHTERING OF ANIMALS - Suryani, Dewi Ervina; Yuslem, Nawir; Khoir, Nispul (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2025)
AbstractThe development of the era and the demands of modern industry have brought about major changes in the procedures for slaughtering animals, one of which is the emergence of mechanical slaughtering methods that are widely used in the global food industry. On the one hand, this method offers efficiency, speed, and cleanliness. On the other hand, doubts and questions arise from Muslims regarding the validity of this method from the perspective of Islamic law. Through qualitative analysis methods of primary and secondary data obtained through literature studies, it was found that there is no clear regulation regarding the mechanical method of slaughtering animals, which has led to doubts and questions from Muslims regarding the validity of mechanical slaughtering. From these findings, it can be concluded that a clear regulation is needed regarding the mechanical slaughter of animals with the standard of maslahah mursalah within the framework of ushul fiqh. Because through this maslahah mursalah, a strict control mechanism, audit, and accountability for the entire slaughtering process are needed. In addition, it is also accompanied by tawthīq (verification) of the halalness of the product which is able to create public trust in the halal industry itself. For this reason, the author suggests that religious authorities and fatwa institutions be proactive in establishing regulations, compiling technical guidelines, and providing education to the public regarding mechanical animal slaughter.Keyword: Animal Slaugther, Mechanical, Islamic Jurisprudence